2009
DOI: 10.1111/j.1365-2672.2008.04101.x
|View full text |Cite
|
Sign up to set email alerts
|

Sphingobacteriumsp. strain PM2-P1-29 harbours a functionaltet(X) gene encoding for the degradation of tetracycline

Abstract: Aims:  The tet(X) gene has previously been found in obligate anaerobic Bacteroides spp., which is curious because tet(X) encodes for a NADP‐dependent monooxygenase that requires oxygen to degrade tetracycline. In this study, we characterized a tetracycline resistant, aerobic, Gram‐negative Sphingobacterium sp. strain PM2‐P1‐29 that harbours a tet(X) gene. Methods and Results:  Sphingobacterium sp. PM2‐P1‐29 demonstrated the ability to transform tetracycline compared with killed controls. The presence of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 17 publications
1
66
0
Order By: Relevance
“…Although recently also found in aerobic Sphingobacterium sp. (Ghosh et al, 2009b) and some Enterobacteriaceae and Pseudomonadaceae strains (Leski et al, 2013), the host diversity of tet(X) is relatively low (Chopra and Roberts, 2001), being mainly carried by Bacteroides (Guiney et al, 1984;Bartha et al, 2011;de Vries et al, 2011;Forslund et al, 2013). As described previously (Tian et al, 2015), Bacteroides was the dominant fermentative bacteria in mesophilic sludge, and experienced fast decline after temperature increase because all species of this genus are mesophilic (Garrity et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recently also found in aerobic Sphingobacterium sp. (Ghosh et al, 2009b) and some Enterobacteriaceae and Pseudomonadaceae strains (Leski et al, 2013), the host diversity of tet(X) is relatively low (Chopra and Roberts, 2001), being mainly carried by Bacteroides (Guiney et al, 1984;Bartha et al, 2011;de Vries et al, 2011;Forslund et al, 2013). As described previously (Tian et al, 2015), Bacteroides was the dominant fermentative bacteria in mesophilic sludge, and experienced fast decline after temperature increase because all species of this genus are mesophilic (Garrity et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As described previously (Tian et al, 2015), Bacteroides was the dominant fermentative bacteria in mesophilic sludge, and experienced fast decline after temperature increase because all species of this genus are mesophilic (Garrity et al, 2004). At the same time, tet(X) has not yet been proved to be horizontally transferred to other strains (Ghosh et al, 2009b), in spite of the fact that it has been linked with a variety of mobile genetic elements (Guiney et al, 1984;Robillard et al, 1985;Shoemaker et al, 1986;Ghosh et al, 2009b). Therefore, the high reduction efficiency of tet(X) during thermophilic AD could be attributed to the elimination of its bacterial host by the high temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of tet(X) in the APW treatment system were 100% identical to those found in the two reported host bacteria Bacteroides and Sphingobacterium. 52,53 Although OTC is considered difficult to biodegrade, 32,54 the high abundance of tet(X) in the activated sludge suggests that tet(X) may have been selected for some unknown function under the high residual OTC levels, which warrants further study. This study revealed for the first time that the relative abundance of tet genes and mobile elements in treated effluent and sludge from the APW treatment system was higher than those in the OTC fermentation residues which have been listed as hazardous wastes (P < 0.01), and higher than STPs and the control systems (P < 0.01), making it essential to manage these routes in relation to ARGs.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Sphingobacteria belonging to the phylym Bacteroidetes was 40.4% and 12.6% for the DWW and the HWW, respectively. Sphingobacteria is known to possess a tetracycline resistance gene which harbors a functional tet (X) gene for the degradation of tetracycline [33,34]. In addition, Sphingobacteria could form a biofilm and contribute to the treatment of ammonium-rich wastewater [35].…”
Section: Microbial Diversity and Comparison In The Dww And The Hwwmentioning
confidence: 99%